1997
DOI: 10.2134/jeq1997.00472425002600010039x
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal (Copper, Lead, and Zinc) Accumulation and Excretion by the Earthworm, Dendrobaena veneta

Abstract: To obtain knowledge about heavy metal kinetics in earthworms (Dendrobaena veneta), we performed accumulation and excretion experiments under laboratory conditions using soils from a heavy metal (Cu, Pb, and Zn)‐contaminated site. To determine heavy metal accumulation rate, earthworms were exposed for 1, 2, 3, 7, 14, 28, 56, or 112 d to soil MH (Cu: 815 mg kg−1, Pb: 340 mg kg−1, and Zn: 225 mg kg−1). After exposure for 28 d to soil LB (Cu 242 mg kg−1, Pb: 109 mg kg−1, Zn 72 mg kg−1) or for 112 d to soil MH, D. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 0 publications
1
18
1
Order By: Relevance
“…Internal Zn concentrations in the earthworm Dendrobaena veneta did not differ from initial concentrations during 56 days of exposure in contaminated field soil (Marinussen et al, 1997b). Oneor two-compartment kinetics models did not fit the data.…”
Section: Zincmentioning
confidence: 68%
See 1 more Smart Citation
“…Internal Zn concentrations in the earthworm Dendrobaena veneta did not differ from initial concentrations during 56 days of exposure in contaminated field soil (Marinussen et al, 1997b). Oneor two-compartment kinetics models did not fit the data.…”
Section: Zincmentioning
confidence: 68%
“…Slow elimination rates of Cu in Marinussen et al (1997b) were explained by Cu binding to chloragosomes, cytoplasmic granules derived from lysosomes in chloragocytes of earthworms (Ireland, 1978). Chloragocytes form a diffuse layer of tissue along the dorsal blood vessel and blood sinuses in earthworms, separating the coelome from the blood.…”
Section: Essential Metalsmentioning
confidence: 99%
“…Some researchers has reported that bioaccumulation of heavy metals by earthworms is metal-specific (Marinussen et al, 1997), as well as earthworm species-specific (Morgan and Morgan, 1999;Hobbelen et al, 2006;Suthar et al, 2008). However, the difference in metal uptake and elimination kinetics between earthworm species is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous authors have suggested that E. fetida is able to regulate Zn by binding Zn in their chloragogenous tissue (Morgan, 1981;Morgan and Morris, 1982;Morgan and Winters, 1982;Cotter-Howells et al, 2005). Since the binding of Zn to metallothioneins is reversible, it was likely that Zn-thioneins may regulate the concentrations of metal in the body tissue by allowing rapid elimination of Zn (van Gestel et al, 1993;Marinussen et al, 1997). Indeed, Zn is an essential element and its internal level is regulated by earthworms; the efficiency of Zn accumulation probably relates to a necessity for a stored pool of available Zn in anticipation of future physiological demand (Nannoni et al, 2011).…”
Section: Metal Accumulation In Earthwormsmentioning
confidence: 99%